2017
DOI: 10.1055/s-0036-1592087
|View full text |Cite
|
Sign up to set email alerts
|

Zygomatic Intraosseous Hemangioma: Case Report and Literature Review

Abstract: Intraosseous hemangiomas are uncommon intrabony lesions, representing approximately 0.5 to 1% of all intraosseous tumors. Their description varies from “benign vasoformative neoplasms” to true hamartomatous proliferations of endothelial cells forming a vascular network with intermixed fibrous connective tissue stroma. These commonly present as a firm, painless swelling. Intraosseous hemangiomas present more commonly in females than in males and most likely occur in the fourth decade of life. The most common et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Primary orbital intraosseous hemangiomas in children are extremely rare. A recent case report and literature review identified 49 reported cases of zygomatic intraosseous hemangioma; only five of the patients were under the age of 18 at diagnosis and only seven were noted to have ocular findings [11]. None of these cases documented a lesion of our size (5 cm × 6 cm) in the zygomatic location.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Primary orbital intraosseous hemangiomas in children are extremely rare. A recent case report and literature review identified 49 reported cases of zygomatic intraosseous hemangioma; only five of the patients were under the age of 18 at diagnosis and only seven were noted to have ocular findings [11]. None of these cases documented a lesion of our size (5 cm × 6 cm) in the zygomatic location.…”
Section: Discussionmentioning
confidence: 98%
“…Biopsy specimens without incorporating the bony component can also be nondiagnostic. Histologic subtypes have been classified as either cavernous, capillary, mixed, or scirrhous on the basis of the size of the vascular spaces and amount of connective tissue within the lesion 2 Case Reports in Ophthalmological Medicine [11,18]. While the diagnosis is often suspected on imaging features and gross examination intraoperatively or of the resected specimen, histopathologic examination is useful in differentiating these tumors from other vascular malformations and immunohistochemical analysis for Factor VIII, vimentin, CD31, and GLUT-1 may be appropriate in select cases [12,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment options included surgical interference in the form of total tumor resection through narrow safety margin with or without reconstruction. Also, non-surgical modality in the form of follow-up after confirming the diagnosis was reported [6]. Reconstruction of the residual zygomatic defects poses a challenge to the surgeons to provide the best esthetic results with a wide variety of treatment options including autogenous bone grafts harvested from iliac crest, rib, and calvaria.…”
Section: Introductionmentioning
confidence: 99%